Electrosynthesis of SER-active silver nanopillar electrode arrays - Feng, Jiu-Ju (2010)
Here we report a one step electrochemical method for the deposition of pillar-like silver nanostructures on graphite plate electrodes. The devices were tested as SER-active electrode arrays using covalently attached hemin. The nanopillar arrays provide reproducible surface enhanced resonance Raman (SERR) signals within 6% standard deviation and Raman enhancement factors of 1 × 105. They also show good electrochemical performance, as verified by potential-dependent SERR spectroscopy and cyclic voltammetry. Furthermore, the hemin-coated arrays display mediatorless electrocatalytic activity toward NO2-. Thus, the Ag nanopillar arrays present good prospects for their application in sensing devices and for SER/SERR based spectroelectrochemical applications in general.